Jornal da Manchete: considerações sobre as linguagens do telejornal - Neves, Renan Cassiano da Silva (Universidade do Vale do Rio dos Sinos, 2021)
This study aims to identify the different languages existing in reports on the Jornal da Manchete program, an attraction of the extinct Manchete Television Network. Therefore, the research performs a theoretical review of some of the main characteristics of Brazilian telejournalism from its origins in the 1950s to the present day. This analysis is based on texts that deal with concepts of television journalism in the country and publications that biographically cite the moments of greatest revolution in television journalism. An analysis process was systematized that took into account the various audiovisual aspects of the coverage. With this base, it was possible to verify peculiarities of the program's reports, detecting strategies in the search for the connection with the viewers and the fulfillment of the social function of a TV newscast.
Keywords: Jornalismo; Telejornalismo; Rede Manchete; Linguagem; Journalism; Television journalism; Language